Antioxidant potential in different parts and callus of Gynura procumbens and different parts of Gynura bicolor - Krishnan, Vijendren; Ahmad, Syahida; Mahmood, Maziah (Hindawi Publishing Corporation, 2015)
Plants from Gynura family was used in this study, namely, Gynura procumbens and Gynura bicolor. Gynura procumbens is well known for its various medicinal properties such as antihyperglycaemic, antihyperlipidaemic, and antiulcerogenic; meanwhile, G. bicolor remains unexploited. Several nonenzymatic antioxidants methods were utilized to study the antioxidant capacity, which include ferric reducing antioxidant power (FRAP), 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay, total flavonoid content, total phenolic content, and ascorbic acid content determination. DPPH assay reveals G. procumbens shoot as the lowest (66.885%) and G. procumbens root as the highest (93.499%) DPPH radical inhibitor. In FRAP assay, reducing power was not detected in G. procumbens leaf callus (0.000 TEAC mg/g FW) whereby G. procumbens root exhibits the highest (1.103 TEAC mg/g FW) ferric reducing power. Total phenolic content and total flavonoid content exhibited similar trend for both the intact plants analysed. In all antioxidant assays, G. procumbens callus culture exhibits very low antioxidant activity. However, G. procumbens root exhibited highest phenolic content, flavonoid content, and ascorbic acid content with 4.957 TEAC mg/g FW, 543.529 QE µg/g FW, and 54.723 µg/g FW, respectively. This study reveals that G. procumbens root extract is a good source of natural antioxidant.